Effect of omega-3 fatty acid supplementation on markers of inflammation and endothelial function in patients with chronic heart disease: A systematic review and meta-analysis: Effects of Omega-3 on heart - Ibrahim Mohialdeen Gubari, Mohammed (Cellular and Molecular Biology, 2024)
Chronic heart disease (CHD) is still a major global cause of morbidity and mortality, necessitating effective therapeutic interventions to mitigate its progression. Omega-3 fatty acids (FAs) have garnered attention for their potential anti-inflammatory and endothelial-protective properties in CHD management. The present study aims to assess the efficacy of Omega-3 FA supplementation on markers of inflammation and endothelial function in patients with CHD. To achieve this, we used the relevant keywords to search international databases (Web of Science, PubMed, Embase, and Scopus) and extract publications evaluating the effectiveness of omega-3 FA supplementation on inflammation markers and endothelial function in patients with CHD. STATA (version 15) and the random and fixed-effects models were used to evaluate the collected data. Thirteen clinical trial studies met inclusion criteria, with a total sample size of 853 individuals (406 cases and 447 controls). The cases had a mean age of 58 ± 10.3 years. The pooled results indicated that omega-3 Omega-3 FA supplementation significantly reduced the level of circulating IL-6 (SMD = -0.47, 95% CI -1.29 to 0.35, %, p < 0.001), hs-CRP (SMD = -0.21, 95% CI -0.70 to 0.28, p = 0.01), and TNF-α (SMD = -0.56, 95% CI -1.14 to 0.01, p < 0.001) in patients with CHD. Also, findings revealed that a daily supplement of omega-3 significantly increased FMD by 0.34% (95% CI: 0.14–0.54%, p < 0.001) as compared with placebo by a fixed-effect model in patients with CHD. These findings underscore the potential therapeutic utility of omega-3 fatty acid supplementation in modulating inflammation and endothelial dysfunction in patients with CHD.